The temporal trends of lightning strikes and their impact on public safety in Nepal - Adhikari, Pitri Bhakta; Shrestha, Anjana; Ghimire, Rachana (BIBECHANA, 2026)
Nepal is a landlocked country with high topographical variation having lowest point 59m and the highest point 8848.86m from the sea level that leads to the high variation in the temperature, climatic condition, and environment that generally leads Nepal to suffer from different natural disaster. Lightning is considered to be the major natural disaster that cannot be controlled. It affects the infrastructures, heritages, national monuments, tall towers of telecommunications and electricity as well as people. This study aims to investigate the effects of Lightning on people. The data are extracted from Disaster Risk Reduction (DRR) portal which includes the number of the people’s death and injured in last thirteen years due to Lightning, annually and monthly. The number of injured individuals exceeded the number of the fatalities by nearly three-fold and no instances of Lightning were observed throughout the month of November.